Chad : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper explores non-oil growth impediments in Chad to better understand why the Chadian economy has not sufficiently rebounded from the crisis. It discusses how the economy is held back by crisis legacies such as high public debt and a fragile banking sector and how Chad continues to face long standing structural weaknesses which hamper potential growth. Three years of recession in Chad have left important legacies that continue to affect fiscal policy and performance in the non-oil private sector and the banking sector. Public domestic debt more than doubled with the crisis. As the Chadian economy was hit by the oil shock, while dramatically cutting spending, the government had to rely on large domestic financing to cushion the impact of the shock. Although the government started paying arrears, the remaining stock is very large and presents a drag on the non-oil economy. The paper ends with a discussion of how Chad's economic potential will require reforms to address those weaknesses to foster economic diversification.